An updated classification for Apocynaceae - Endress, Mary E.; Liede-Schumann, Sigrid; Meve, Ulrich (Phytotaxa, 2014)
An updated suprageneric classification is provided for Apocynaceae to bring the family into better agreement with recent morphological and molecular, mainly phylogenetic-based, results. A total of 366 genera are recognized and placed within five subfamilies, 25 tribes and 49 subtribes. In Apocynaceae s. str., one new tribe (Amsonieae) and two new subtribes (Tonduziinae and Vincinae) are described in Rauvolfioideae, and one new tribe (Rhabdadenieae) and nine new subtribes (Amphineuriinae, Beaumontiinae, Chonemorphinae, Galactophorinae, Papuechitinae, Peltastinae, Pentalinoninae, Prestoniinae and Urceolinae) are described or validated in Apocynoideae. Within Asclepiadoideae, one new tribe (Eustegieae) and three subtribes (Diplolepinae, Pentacyphinae and Tassadiinae) are described or validated.